RANCANG BANGUN APLIKASI ARSIP AKTA KEPENDUDUKAN BERBASIS WEB PADA DINAS KEPENDUDUKAN DAN CATATAN SIPIL KOTA PONTIANAK - Eri Bayu Pratama; Ardi Setia Nugraha; Ade Hendini (STMIK KAPUTAMA, 2021)
The information technology accelerates so fast. The computer is a device that was created to facilitate human work and help achieving good progress in the manufacture of hardware and software. Dinas Kependudukan dan Catatan Sipil Kota Pontianak does need an existence of an information system that supports and provides satisfactory service for society. For that reason the writer tries to make the final task about The Web-Based Application of Population’s Archives Management in Dinas Kependudukan dan Catatan Sipil Kota Pontianak, which until now has not been computerized. At this time Dinas Kependudukan dan Catatan Sipil Kota Pontianak is a service in charge of serving the community in terms of stewardship of letters that are private or state documents. The existing system in Dinas Kependudukan dan Catatan Sipil Kota Pontianak is still done manually, starting from keeping, arranging and searching the archives, it is possible for the workers to search archives using the numbers in every storage rack and it will spend a lot of time and energy especially when the archives are needed quickly. The Web-Based Application of Population’s Archives Management is the best solution to solve these kind of problems - the problems that exist in this company will be solved by using a computerized system, this company will also gain an effective and efficient activities. By any means this computerized system will help the run of this company in the future. The computerized system is better than the manual system to run more effectively and efficiently and now managing population’s archives will be more conducive than ever before.